IMPROVING STUDENTS’ SPEAKING SKILL THROUGH ROLE PLAY TECHNIQUE ON ELEVENTH GRADE STUDENTS - Soraya, Aida; Sofian, Sofian; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research was aimed to improve students’ speaking problem through Role Play on class XI IPA 1 of MAN Putussibau in academic year 2016/2017. In this research, the writer implemented Role Play to solve the students’ problem. The 33 students were participating in this research. The method of this research was Classroom Action Research. The students’ attitude towards the learning process were gathered by observation checklist and fieldnote. The data of speaking skill were obtained by speaking assessment according to the scoring rubric. In each cycle, the students improved their speaking skill through Role Play, especially in the last step, practicing and reviewing. According to the finding, the students were not able to pronounce some words and not fluent in speaking in the first cycle. They started to improve their speaking in the second cycle. In the cycle three, the students were able to pronounce the words and fluent when performed the Role Play. As the conclusion, Role Play improved the students’ speaking problem. For English teachers, Role Play can be used to improve students’ problem in speaking. Keywords: Role Play, Speaking Skill, Classroom Action Research